Carbon Nano Tube Field Effect Transistors Based Ternary Ex-OR and Ex-NOR Gates - Patcha, Kavitha; Musala, Sarada; Vijayavardhan, K.; Sudha Vani, Y.; Srinivasulu, Avireni (Current Nanoscience, 2016)
Background: A carbon nanotube field-effect transistor (CNTFET) is, however a field-effect transistor itself, which utilizes a single carbon nanotube or a multiple of carbon nanotubes act as the channel material instead of bulk silicon in the traditional MOSFET structure. A carbon nanotube is a tube-shaped material, made of carbon, having a diameter measuring on the nanometer scale. Multi-Valued Logic (MVL) is a calculus in which there exist more than two truth values. The ternary logic is a common MVL, which includes three significant logic levels. These logic levels are ‘0’, ‘1’ and ‘2’ symbols respectively. As such three different types of logics are used for the ternary logic, those include negative, positive and standard. The purpose of this paper is to introduce a new low-power ternary logic Ex-OR and Ex-NOR gates using CNTFETs. The proposed ternary logic circuits are designed based on the conventional static CMOS and pseudo nMOS architectures. Moreover, each of the proposed CNTFET based ternary logic gates includes all the possible types of ternary logic, that is, negative, positive and standard. Methods/Results: All the proposed ternary Ex-OR and Ex-NOR gates are simulated using Spectre Cadence with the supply rail voltage of +0.9 V using 32 nm CNTFET technology files. The transient response of all the CNTFET static and pseudo ternary Ex-OR and Ex-NOR logic gates are reviewed. The power consumption and the propagation delays of all the proposed Ex-OR and Ex-NOR circuits are calibrated. The results have indicated that the delays of pseudo gates are considered less than normal gates. Conclusion: In this paper CNTFET-based 2-input Ex-OR and Ex-NOR gate design are presented. The proposed CNTFET-based circuits have been designed by deploying multi-valued logic (ternary logic) and multiple threshold voltage nano devices. These circuits are designed at various carbon nanotube diameters having less than 3 nm. The simulation results confirm the authenticity and the superiority of the proposed circuits in terms of the propagation delays and power consumption. So, these are proven to be the best choice for low-power and low-voltage applications that require of small area, high performance, high noise margin and low power dissipation.
Keywords: Negative Ternary